2005
DOI: 10.1249/01.mss.0000177466.01232.7e
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Uptake Dynamics: From Muscle to Mouth—An Introduction to the Symposium

Abstract: The purpose of this paper is to provide an introduction to the study of oxygen uptake (VO(2)) dynamics or kinetics. Following the onset of exercise, both muscle and pulmonary VO(2) rise in a near-exponential fashion towards the anticipated "steady-state" VO(2) demand. However, it can take 2-4 min, or even longer at higher work rates, before this steady state is attained. Slow VO(2) kinetics increase the so-called O(2) deficit and obligate a greater contribution from anaerobic mechanisms of ATP production (invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
112
2
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(124 citation statements)
references
References 61 publications
2
112
2
5
Order By: Relevance
“…In a recent placebocontrolled study, we reported that beetroot juice supplementation significantly reduced the O 2 cost of treadmill walking and improved exercise tolerance in healthy young adults (47). These results are remarkable because the V O 2 -work rate relationship has traditionally been considered to be independent of age, health status, and aerobic fitness (36). The reduction in the O 2 cost of moderate-intensity exercise following dietary NO 3 Ϫ supplementation may be a result of a reduced ATP cost of muscle force production (5) and/or enhanced mitochondrial efficiency (51).…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…In a recent placebocontrolled study, we reported that beetroot juice supplementation significantly reduced the O 2 cost of treadmill walking and improved exercise tolerance in healthy young adults (47). These results are remarkable because the V O 2 -work rate relationship has traditionally been considered to be independent of age, health status, and aerobic fitness (36). The reduction in the O 2 cost of moderate-intensity exercise following dietary NO 3 Ϫ supplementation may be a result of a reduced ATP cost of muscle force production (5) and/or enhanced mitochondrial efficiency (51).…”
mentioning
confidence: 85%
“…Faster V O 2 kinetics would be expected to reduce the reliance on nonoxidative metabolic processes across the transition from a lower to a higher metabolic rate and, therefore, to reduce muscle metabolic perturbation (i.e., changes in substrates or metabolites that have been associated with fatigue development; Ref. 36,82). In the present study, the O 2 deficit was reduced by 15% following NO 3 Ϫ supplementation, as a function of the faster V O 2 kinetics.…”
Section: Effects Of Nitrate Supplementation On the Physiological Respmentioning
confidence: 99%
“…24,55). For heavy-intensity work rates that lie between L and critical power [CP; i.e., the power asymptote of the power-duration (P-t) relationship], the emergence of an additional delayed "slow component" (V O 2 sc) results in V O 2 attaining an eventual steady-state value greater than that predicted from the sub-L V O 2 -work rate relationship (reviewed in Refs.…”
Section: Concentration ([Lmentioning
confidence: 99%
“…For heavy-intensity work rates that lie between L and critical power [CP; i.e., the power asymptote of the power-duration (P-t) relationship], the emergence of an additional delayed "slow component" (V O 2 sc) results in V O 2 attaining an eventual steady-state value greater than that predicted from the sub-L V O 2 -work rate relationship (reviewed in Refs. 24,55), and whose origin has been demonstrated to reside predominantly within the working musculature (39,43,46). CP is thought to be equivalent to the highest work rate for which a steady-state of V O 2 , [L Ϫ ]a, and acidic pHa can be achieved [22,40,55; although see Housh et al (23) for an alternative view] and may, therefore, be regarded as reflecting a rate of aerobic energy pool reconstitution that dictates the maximum power that can be sustained without a progressively increasing anaerobic contribution (35,40,56).…”
Section: Concentration ([Lmentioning
confidence: 99%
See 1 more Smart Citation